2020
DOI: 10.1177/0363546520931831
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Anatomic Features Linked to Anterior Cruciate Ligament Injuries During Skeletal Growth and Maturation

Abstract: Background: Several anatomic features of the knee have been shown to affect joint and anterior cruciate ligament (ACL) loading and the risk of subsequent injuries. While several studies have highlighted sex differences between these anatomic features, little is known on how these differences develop during skeletal growth and maturation. Hypotheses: (A) Anatomic features linked to an ACL injury will significantly change during skeletal growth and maturation. (B) The age-related changes in anatomic features lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 44 publications
0
33
0
1
Order By: Relevance
“…Females are apt to have ACL injuries than males, and the anatomical structures were different in females compared to males (41). The results of Wolters et al (42) showed a narrower intercondylar notch in women, whereas results from Eck et al (43) concluded that there were no differences in NWI between genders.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Females are apt to have ACL injuries than males, and the anatomical structures were different in females compared to males (41). The results of Wolters et al (42) showed a narrower intercondylar notch in women, whereas results from Eck et al (43) concluded that there were no differences in NWI between genders.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, Due to the characteristic of our study, the number of female and male participants was unequal. The difference in gender can lead to different results in the prevalence of ACL injuries and meniscal injuries as previously reported (41,44,45). Restricted by the limited time and resources, our study did not include the height and weight of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research shows that about 40% of all ligamentous knee injuries are related to anterior cruciate ligament (ACL) injuries, while about 70% of ACL injuries occur during sports activities [ 1 ]. As a matter of fact, an ACL injury is a non-contact injury that is in association with sports activities [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…When the ACL is completely torn, due to a lack of self-healing process in the ligaments [ 2 , 3 ], the reconstruction surgery should be used [ 4 ]. The Swedish National ACL Register reported for about half the ACL injuries reconstruction is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars such as Wilson et al, Clatworthy et al and Fahey et al [ 5 7 ] proposed that the graft is most likely to be damaged in 4–8 months after the reconstruction, and the enlargement of the inner diameter of the tunnel occurred in 3 months after the operation. Previous studies have described imaging features linked to the stability of the knee and ACL injury [ 8 ].…”
Section: Introductionmentioning
confidence: 99%